Experimental investigation on the hydrodynamic performance of a cylindrical dual-chamber Oscillating Water Column device. (15th February 2020) - Ning, De-zhi; Zhou, Yu; Mayon, Robert; Johanning, Lars
Highlights: An experimental study on a cylindrical dual-chamber OWC device was carried out. The outer chamber can improve the hydrodynamic performance of the OWC device. There exist two different resonant frequencies in the inner- and outer- chambers. The hydrodynamic efficiency of the device decreases as the wave steepness increases. Abstract: The hydrodynamic performance of a stationary cylindrical dual-chamber Oscillating Water Column (OWC) wave energy device was experimentally studied to assess conversion efficiency in comparison with a single-chamber OWC. The contribution of the present work is to guide the design and optimization of the dual-chamber OWC device for efficiently capturing offshore wave energy. The effects of various parameters including wave steepness, the opening ratio, the inner- and outer-chamber drafts on the hydrodynamic efficiency of the proposed OWC device were considered. It was found that the hydrodynamic efficiency of the dual-chamber OWC device increases by comparison with the single-chamber one. A coupled resonant effect between the inner- and outer-chambers was observed for the dual-chamber OWC, which leads to the difference between the resonant frequencies and broadens the effective frequency bandwidth. The ratio of the orifice opening area to the area of the chamber columns has a significant influence on the hydrodynamic efficiency. The optimal opening ratio is founded to be between 1.5% and 2.0% in the present study. It was also observed that the hydrodynamic efficiency decreases with the increase of wave steepness and increases with the decrease of the outer-chamber draft.